Transitions of Care from Child and Adolescent Mental Health Services to Adult Mental Health Services (TRACK Study): A study of protocols in Greater London - Ford Tamsin; Paul Moli; Singh Swaran P; Kramer Tami; Weaver Tim (BMC, 2008)
Abstract Background Although young people's transition from Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS) in England is a significant health issue for service users, commissioners and providers, there is little evidence available to guide service development. The TRACK study aims to identify factors which facilitate or impede effective transition from CAHMS to AMHS. This paper presents findings from a survey of transition protocols in Greater London. Methods A questionnaire survey (Jan-April 2005) of Greater London CAMHS to identify transition protocols and collect data on team size, structure, transition protocols, population served and referral rates to AMHS. Identified transition protocols were subjected to content analysis. Results Forty two of the 65 teams contacted (65%) responded to the survey. Teams varied in type (generic/targeted/in-patient), catchment area (locality-based, wider or national) and transition boundaries with AMHS. Estimated annual average number of cases considered suitable for transfer to AMHS, per CAMHS team (mean 12.3, range 0-70, SD 14.5, n = 37) was greater than the annual average number of cases actually accepted by AMHS (mean 8.3, range 0-50, SD 9.5, n = 33). In April 2005, there were 13 active and 2 draft protocols in Greater London. Protocols were largely similar in stated aims and policies, but differed in key procedural details, such as joint working between CAHMS and AMHS and whether protocols were shared at Trust or locality level. While the centrality of service users' involvement in the transition process was identified, no protocol specified how users should be prepared for transition. A major omission from protocols was procedures to ensure continuity of care for patients not accepted by AMHS. Conclusion At least 13 transition protocols were in operation in Greater London in April 2005. Not all protocols meet all requirements set by government policy. Variation in protocol-sharing organisational units and transition process suggest that practice may vary. There is discontinuity of care provision for some patients who 'graduate' from CAMHS services but are not accepted by adult services.